Historical dictionary of journalism - Eaman, Ross Allan, 1945- (Historical dictionaries of professions and industries., 2021)
"Historical Dictionary of Journalism, Second Edition covers 46 countries, it contains a chronology, an introduction, an extensive bibliography, and more than 300 cross-referenced entries on a wide array of topics, such as African-American journalism, the historiography of the field, the New Journalism, and women in journalism"--